Late and Postglacial Paleoenvironments of the Gulf of St. Lawrence: Marine and Terrestrial Palynological Evidence - de Vernal, Anne; Guiot, Joël; Turon, Jean-Louis (Géographie physique et Quaternaire, 1993)
ABSTRACTCored sediments from Anticosti and Esquiman channels and from Cabot Strait have been analyzed for their palynological content, which includes pollen and spores and dinoflagellate cysts. The dinoflagellate cyst assemblages led to the establishment of a regional ecostratigraphy and to quantitative reconstruction of changes in sea-surface conditions using transfer function (best analogue method). Prior to about 10,000 BP, assemblages dominated by Brigantedinium are associated with relatively cold (4-100C in August) surface water and extensive seasonal sea-ice cover (up to 8 months/yr.); in Cabot Strait low salinity conditions (25-27%o) were recorded from about 11,800 to 10,000 BP as the result of outflow of meltwater discharge from the Laurentide Ice Sheet. Between ca. 11,000 and 10,500 BP a cooling phase in surface water probably corresponds to the Younger Dryas event. At about 10,000 BP, a sharp transition marked by the occurrence of abundant Gonyaulacales, corresponds to the establishment of conditions similar to the present with summer temperatures up to 160C, salinity of -31 %o and a seasonal extent of sea-ice of about 2 months/yr. During the Holocene, slight fluctuations of sea-surface temperature are reconstructed, and a thermal optimum is recorded at about 6000 BP. The pollen and spore assemblages led to direct correlations with the onshore palynostratigraphy. In the northern Gulf region, Picea migration apparently rapidly followed the early Holocene surface water warming although the development of closed coniferous forests occurred much later. In the southern part of the Gulf, the Picea forest expansion coincides with the early Holocene increase of temperature, and the significant occurrence of Tsuga followed the middle Holocene thermal optimum as recorded in sea-surface water.